2013
DOI: 10.1371/journal.pone.0070437
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch Increases MMP-2 Production in Vascular Smooth Muscle Cells via Activation of PDGFR-β/Akt Signaling Pathway

Abstract: Increased blood pressure, leading to mechanical stress on vascular smooth muscle cells (VSMC), is a known risk factor for vascular remodeling via increased activity of matrix metalloproteinase (MMP) within the vascular wall. This study aimed to identify cell surface mechanoreceptors and intracellular signaling pathways that influence VSMC to produce MMP in response to mechanical stretch (MS). When VSMC was stimulated with MS (0–10% strain, 60 cycles/min), both production and gelatinolytic activity of MMP-2, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 41 publications
6
30
0
Order By: Relevance
“…Therefore, we hypothesized that OPN produced in VSMC exposed to MS might regulate MMP production in vasculature. Consistent with the findings of our previous study, in which MS increased MMP-2, but not MMP-9 production in VSMC [36], the present study also showed mice were treated with Ang II or L-LAME for 13 days to increase blood pressure, and then aorta was isolated to determine MMP-2 production. Immunohistochemical stain of MMP-2 in the aorta of Ang II-induced hypertensive mice (A) or L-NAME-induced hypertensive mice (B) was compared with that of control mice (Veh).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we hypothesized that OPN produced in VSMC exposed to MS might regulate MMP production in vasculature. Consistent with the findings of our previous study, in which MS increased MMP-2, but not MMP-9 production in VSMC [36], the present study also showed mice were treated with Ang II or L-LAME for 13 days to increase blood pressure, and then aorta was isolated to determine MMP-2 production. Immunohistochemical stain of MMP-2 in the aorta of Ang II-induced hypertensive mice (A) or L-NAME-induced hypertensive mice (B) was compared with that of control mice (Veh).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous reports [22] and support a role of MMPs in the uteroplacental and vascular remodeling associated with Norm-Preg. Importantly, MMPs immunostaining was particularly apparent in the aortic media, consistent with reports that vascular smooth muscle cells (VSMCs) are a major source of MMPs [36, 37]. …”
Section: Discussionsupporting
confidence: 87%
“…Arteries submitted to increased transmural pressure showed increased MMP-2 activity and elastin proteolysis [32]. Mechanical stress increased MMP-2 in VSMCs by activating the platelet-derived growth factor mechanoreceptor (PDGF-R) and protein kinase B/Akt signaling pathways [34] (fig. 1b).…”
Section: Regulation Of Transcription and Activity Of Mmp-2 In Hypertementioning
confidence: 99%